High-intensity interval training's effect on acute physiological stress responses and esports performance - Pakarinen, Kia (2023)
This Master’s thesis aimed to investigate the high-intensity interval training (HIIT) acute effects on physiological stress responses and esports performance markers. Esports and exercise are commonly seen as antagonistic activities due to esports’s inactive nature. However, exercise has been seen potential beneficial effects in useful markers in esports, like cognitive function and esport performance markers, which could potentially encourage esports athletes to participate in physical activity. Esports athletes are also exposed to high stress responses, and if prolonged, can cause health defects. Exercise on the other hand has shown beneficial effects on stress responses. This Master’s thesis study was conducted as an intra-subject study, in which the subjects participated in exercise and resting models. The study was divided into three days: preliminary measurements, exercise model and resting model. The subjects participated in all phases. Preliminary measurements the subjects answered electrical Webropol questionnaires about their health, health habits and gaming habits, and participated in bioimpedance body composition measurement and maximal oxygen uptake cycle ergometer test. In the exercise model, the subjects conducted a 15-minute HIIT protocol, after which they answered to a mood state questionnaire and did a cognitive reboot reading a book for 20 minutes. After reading session, the subjects did a simulated esports performance in Counter Strike: Global Offensive game, within AimBotz aim training map. During the research, the subjects were monitored of heart rate, heart rate variability and salivary stress markers (cortisol, alpha-amylase and dehydroepiandrosterone sulfate). In resting model, the same subjects sat on an cycle ergometer in rest for 15 minutes, and conducted all the other measurements identical to exercise model. 7 days after the last intervention day, the subjects were forwarded a physical activity enjoyment questionnaire (Webropol) via email. Salivary stress marker analysis was conducted on enzyme-linked immunosorbentassay method, and heart rate variability analysis with Kubios. Statistical significance was assessed with RStudio using nonparametric methods (Friedman and Wilcoxon). Within-day differences in salivary cortisol were found statistically significant. Moreover, differences between the exercise and resting models and control in salivary alpha-amylase were also found statistically significant. The differences between exercise and resting models in average in-game heart rate were found statistically significant. Esports performance, mood states and mood disturbances didn’t show statistically significant differences. The results would indicate differentiated responses from different stress response systems, with an attenuated response from hypothalamic-pituitary-adrenal axis, and an incerased response from sympathoadrenal-medullary system with a potential enhancing effect to esports-induced stress responses. More studies are required to examine the effects of different exercise modalities in stress responses in esports and effects on esports performance.